1986
DOI: 10.1017/s000335610001792x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a combined androgenic-oestrogenic anabolic agent in steers and bulls 2. Muscle weight distribution, partition of body fat and carcass value

Abstract: Twenty-one pairs of male cattle twins, 10 of which were monozygotic, were used in a study of the effects of a combined implant of trenbolone acetate (140 mg) and oestradiol-17β (20 mg) on muscle distribution, fat partition and carcass value. There were three comparisons within pairs: (1) between bulls and steers (no implants); (2) between bulls and implanted steers; and (3) between bulls and implanted bulls.Implants were given twice, at 44 to 73 and 300 days of age, and animals were slaughtered at 400 days fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…The only clear effect of sex on muscle growth and distribution was in the neck and thorax muscle group, entire males having a faster relative growth and heavier weight of muscle than females. These results suggest no difference in the maturing characteristics of the musculature in males and females, and that the differences in the neck and thorax were caused by sex hormones as in cattle (Wood, Fisher & Whelehan, 1986). Furthermore, the muscle distribution and growth patterns do not support the view that entire males have an inferior muscle distribution which would lower carcass quality in comparison with the other 'sexes'.…”
Section: Development and Distribution Of Musclementioning
confidence: 77%
“…The only clear effect of sex on muscle growth and distribution was in the neck and thorax muscle group, entire males having a faster relative growth and heavier weight of muscle than females. These results suggest no difference in the maturing characteristics of the musculature in males and females, and that the differences in the neck and thorax were caused by sex hormones as in cattle (Wood, Fisher & Whelehan, 1986). Furthermore, the muscle distribution and growth patterns do not support the view that entire males have an inferior muscle distribution which would lower carcass quality in comparison with the other 'sexes'.…”
Section: Development and Distribution Of Musclementioning
confidence: 77%
“…The effect of male sex hormones associated with the often difficult temperament of entire horses may increase the likelihood of tendon injury. Alternatively, differences in body composition, including greater forequarter size, have been reported in entire males of other species compared to geldings (Watson 1969;Wood et al 1986). Similar differences in entire horses may increase the likelihood of SDF tendon injury.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown however that, in sheep, the rate of synthesis in the vastus intermedius muscle in the hind leg is higher than in the neighbouring vastus lateralis and in the longissimus dorsi in the back (Bryant & Smith 1982;. The comparative slaughter experiment of Wood et al (1986) showed that, in steers treated with a combined implant of trenbolone acetate and oestradiol, there was preferential deposition of protein in the forequarter muscles compared with the muscles of the back and . hindquarter; but whether this was the result of a relative increase in synthesis or a decrease in degradation in the forequarter is not known.…”
Section: Discussionmentioning
confidence: 99%